Use of alternative polyadenylation sites for tissue-specific transcription of two angiotensin-converting enzyme mRNAs. - Thekkumkara, T J (1992)
The pulmonary isozyme of rabbit angiotensin-converting enzyme (ACE) is encoded by an mRNA of about 5 kb. cDNA clones corresponding to different parts of this mRNA have been isolated and the complete nucleotide sequences of both the coding and non-coding regions of the mRNA have been determined. The encoded protein has 1309 residues with a 33 amino acids-long signal peptide at the amino terminus and a potential membrane-anchoring domain near the carboxyl terminus. There is a strong sequence homology between two regions of the rabbit cDNA and between the rabbit, human, and mouse cDNAs. Comparison of the nucleotide sequences of the 3' untranslated regions of rabbit pulmonary and testicular ACE cDNAs revealed that the testicular cDNA is nested within the pulmonary cDNA at the 3' end. A rabbit genomic clone encompassing this region was isolated and partially sequenced. It was shown that the gene contains two potential polyadenylation sites 628 bp apart within one exon. Northern analyses with an appropriate oligonucleotide probe confirmed that the proximal polyadenylation site is used exclusively for terminating the testicular mRNA whereas the distal one is used exclusively for the pulmonary mRNA. These results demonstrated that the transcription of the two mRNAs encoding the two ACE isozymes not only initiates at two alternative tissue-specific sites which are 5.7 kb apart but the mRNAs also get polyadenylated at two alternative sites which are 628 bp apart.